2022
DOI: 10.3390/ani12131616
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations within the Bovine CRY2 Gene Are Significantly Associated with Carcass Traits

Abstract: As an important part of the circadian rhythm, the circadian regulation factor 2 of cryptochrome (CRY2), regulates many physiological functions. Previous studies have reported that CRY2 is involved in growth and development. However, the relationship between CRY2 gene polymorphism and cattle carcass traits remains unclear. The aim of this study was to detect the possible variations of the CRY2 gene and elucidate the association between the CRY2 gene and carcass traits in the Shandong Black Cattle Genetic Resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previously, Su et al discovered that an 18 bp deletion in intron 2 of PDGFD was associated with litter size for Australian white sheep [25]. Data from the Ruminant Genome and NCBI databases showed that PDGFD is highly expressed in the reproductive system (i.e., ovary) [25]. These results imply that PDGFD may control multiple traits simultaneously (i.e., gene pleiotropism).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Su et al discovered that an 18 bp deletion in intron 2 of PDGFD was associated with litter size for Australian white sheep [25]. Data from the Ruminant Genome and NCBI databases showed that PDGFD is highly expressed in the reproductive system (i.e., ovary) [25]. These results imply that PDGFD may control multiple traits simultaneously (i.e., gene pleiotropism).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kang et al discovered that a 7 bp InDel variation in intron 8 of lysine demethylase 3B (KDM3B) not only affected the litter size of Australian white sheep, but was also significantly associated with the body size traits of Lanzhou fat-tailed sheep and Luxi black-headed sheep [41,42]. Previously, Su et al discovered that an 18 bp deletion in intron 2 of PDGFD was associated with litter size for Australian white sheep [25]. Data from the Ruminant Genome and NCBI databases showed that PDGFD is highly expressed in the reproductive system (i.e., ovary) [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three upstream gene variants were screened from the Ensembl database, and then several primers ( Table 1 ) were designed using Primer Premier 5 software and synthesized by Sangon Biotech (Xi'an, China) based on reference sequences in ovine HIAT1 (NC 056054.1). Polymorphic fragments were amplified using the polymerase chain reaction (PCR) method and utilized a touch-down program and reaction volumes as described in previous studies ( 8 , 22 ). PCR products were then separated by electrophoresis on a 3.5% agarose gel stained with GoldView.…”
Section: Methodsmentioning
confidence: 99%